[PP.13.01] THE TREATMENT BENEFIT OF THE ACE-INHIBITOR PERINDOPRIL ON TOP OF BETA-BLOCKER THERAPY IN PATIENTS WITH VASCULAR DISEASE. (September 2016) - Brugts, J.; Bertrand, M.; Remme, W.; Ferrari, R.; Fox, K.; MacMahon, S.; Chalmers, J.; Simoons, M.; Boersma, H.
Abstract : Objective: Angiotensin-converting enzyme (ACE) inhibitors have been shown to reduce cardiovascular events and mortality in different groups of patients. As they are often combined in clinical practice to beta-blockers, we undertook an analysis using individual data from ADVANCE, EUROPA, and PROGRESS to determine the benefit of the combination of beta-blockers with perindopril in patients with cardiovascular disease or at high risk of cardiovascular disease. Design and method: In patients participating in the ADVANCE, EUROPA and PROGRESS trials which were randomized to an ACE-inhibitor based regimen or placebo, we identified all patients who received beta-blocker at baseline. We studied the effect of perindopril on top of beta-blockers on cardiovascular outcomes and mortality with a multi-variate Cox regression analysis. Results: At baseline, 39% of patients in the three studies received beta-blocker (n = 11418 among 29463 patients). Blood pressure reduction during the run-in period was similar between patients receiving perindopril on top of beta-blocker compared with patients receiving perindopril without beta-blocker at baseline (respective SBP/DBP reduction of −7.9/−3.6 mmHg and −8.8/−4.0 mmHg). The composite endpoint of cardiovascular mortality, non-fatal myocardial infarction and stroke was significantly reduced by 20% in the group of patients receiving beta-blocker/perindopril compared with those with beta-blocker/placebo (HR 0.80, 95% CI: 0.71–0.90). In addition, the benefit on this composite endpoint was similar whether patients were hypertensive (HR 0.77, 95% CI: 0.66–0.89) or not hypertensive (HR 0.84, 95% CI: 0.71–1.00). Other endpoints such as myocardial infarction (HR 0.77, 95% CI: 0.65–0.91), cardiovascular mortality (HR 0.73, 95% CI: 0.61–0.85) and all-cause mortality (HR 0.78, 95% CI: 0.68–0.88) were also significantly reduced in the beta-blocker/perindopril group vs beta-blocker/placebo. Conclusions: Addition of perindopril to a beta-blocker in a broad spectrum of patients with vascular disease or high risk of vascular disease significantly improves survival and lowers the risk of myocardial infarction.